The Future of War : The Re-Enchantment of War in the Twenty-First Century - Coker, Christopher (GHQ, Rawalpindi Army Eduction Publishing, 2006)
Coker offers a new & provocative thesis about the future of war, arguing that biotechnology has provided the institution with a new lease of life.
Include Notes and Index
Keywords: War--Forecasting -- War